Dynamic analysis and optimization design of a planar slider–crank mechanism with flexible components and two clearance joints. (May 2016) - Li, Yuanyuan; Chen, Guoping; Sun, Dongyang; Gao, Yong; Wang, Ke
Abstract: This paper conducts a numerically comparative study on dynamic response of a planar slider–crank mechanism with two clearance joints between considering harmonic drive and link flexibility, and investigates the effect of harmonic drive on dynamic behavior of the mechanism with different location of single clearance joint and with two clearance joints respectively. The comparative study of optimization design of the rigid and harmonic drive slider–crank mechanism experiencing wear is also presented. To estimate the contact forces and pressures, the elastic foundation model (EFM) with hysteresis damping is employed. The harmonic drive considering nonlinear spring-damp and flexibility of harmonic gear is used. Additionally, the response surface meta-model, as a cost-effective mathematical tool, is built for optimizing the system's performance. Simulation results show that application of harmonic drive can more effectively suppress the output peak than that of flexible link, and the suspension effect of harmonic drive is decreased with the increasing number of gap joint. Optimization results indicate the change of wear performance of the mechanism driven by harmonic drive is gradual relative to the rigid mechanism. Furthermore, when reaching wear limit for the two clearance joints simultaneously the working time of the harmonic drive slider–crank mechanism is longer. Highlights: Suspension effect of harmonic drive is superior to component flexibility. Increasing of the number of gap joints reduces damping effect of harmonic drive. Position of the single gap joint affects the suspension effect of harmonic drive. Wear performance of multibody system is quite sensitive to bushing depth. Optimization results with application of harmonic drive are more gradual.